Menguak Skeptisisme Profesional Auditor: Pilar Kualitas Audit atau Beban Efisiensi? - Nazari, Esa Cahyani; Kirana, Rina Tjandra (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Auditor professional skepticism is a key aspect in determining audit quality and audit process efficiency. This study aims to analyze the role of auditor professional skepticism in improving audit quality and the challenges that arise in its implementation. Using a qualitative approach through the Systematic Literature Review (SLR) method, this study reviewed 36 relevant articles from various national and international journals. The results show that 25 studies support professional skepticism as a major factor in improving audit quality. Skeptical auditors are able to detect material errors and indications of fraud more accurately, increase the transparency of financial statements, and strengthen corporate accountability. However, another 11 studies highlighted that excessive professional skepticism can hinder audit efficiency by extending audit duration, increasing costs, and creating tension with clients. In addition, time budget pressures and efficiency demands may reduce the application of auditor skepticism in some circumstances. The success of auditors' professional skepticism depends not only on high applicability, but also balance with audit efficiency. Factors such as auditor experience, external pressures, and applicable regulations are key elements in determining the effectiveness of professional skepticism in audits. Therefore, the professional skepticism implementation strategy should be tailored to the specific needs and characteristics of the audit to ensure a quality audit without hampering efficiency.